Efficacy and safety of statin therapy in multimorbid outpatients with very high cardiovascular risk - N. V. Izmozherova; A. A. Popov; V. M. Bakhtin (Российский кардиологический журнал)
Aim. To analyze the efficacy and safety of statin therapy in multimorbid outpatients with very high cardiovascular risk in actual clinical practice.Material and methods. The study included 131 patients with an established very high cardiovascular risk. History and anthropometric data were collected. The Charlson Comorbidity Index (CCI) was calculated; patients were divided into groups of moderate (№ 1, ≤6 points) and high (№ 2,> 6 points) multimorbidity. The frequency of prescribing statins, the range of doses used, the achievement of lipid metabolism targets, and the incidence of adverse effects were evaluated.Results. The median of the CCI was 6 (5÷8) points. Group 1 included 72 patients, group 2 — 59 patients. Statins received 87 (66,4%) patients, more often in group 1 (n=54) than 2 (n=33), p=0,026. The minimum doses were taken by 17 patients, the mean — 66, the maximum — 4. Patients of group 2 received higher dosages (χ2 =9,3, p=0,010). The target level of total cholesterol was achieved in 8 (6,1%) patients, low-density lipoprotein cholesterol — no one (0,0%). Of the 106 patients ever taking statins, they were withdrawn in 19 (17,9%) patients. The reason for discontinuation in 7 patients were adverse effects, in 5 — the high cost of therapy; in 7 patients, the reason was identified. Adverse effects were recorded in 12 (11,3%) patients; there were no differences between groups (p=0,118).Conclusion. Patients with a very high cardiovascular risk are characterized by high multimorbidity. Statins are less commonly prescribed for patients with severe polymorbidity, but at higher doses. Despite the sufficient prescribing statins and the use of mean doses, target lipid levels were not achieved. The presence of multimorbidity was not associated with an increase in the incidence of statin adverse effects.